2021
DOI: 10.1039/d1ob01871j
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced assembly of the 3,4,4a,7a-tetrahydro-1H-cyclopenta[b]pyridine-2,7-dione core on the basis of allomaltol derivatives

Abstract: A novel photochemical synthetic pathway to various substituted 3,4,4a,7a-tetrahydro-1H-cyclopenta[b]pyridine-2,7-diones based on readily available allomaltol derivatives containing an amide group was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…It should be mentioned that studied photoreaction is similar to the previously published cyclization of 3-hydroxypyran-4-one derivatives containing an amide group. [17] Wherein, the final step in the present communication is different and includes reaction with hydroxyl group leading to the formation of tetrahydrofuran ring.…”
Section: Chemistryselectmentioning
confidence: 98%
See 3 more Smart Citations
“…It should be mentioned that studied photoreaction is similar to the previously published cyclization of 3-hydroxypyran-4-one derivatives containing an amide group. [17] Wherein, the final step in the present communication is different and includes reaction with hydroxyl group leading to the formation of tetrahydrofuran ring.…”
Section: Chemistryselectmentioning
confidence: 98%
“…Further capture of the aforementioned labile intermediates allows the synthesis of diverse heterocyclic systems. It should be noted that such trapping can be carried out either under action of the additional reagents [13,14] or intramolecularly using functional groups of the side chain [15,17] (Scheme 1, A). Earlier we have shown that the ester and amide fragments can be used in this capacity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative approach for trapping of such unstable intermediates is the preliminary introduction of functional groups into the 3-hydroxypyran-4-one structure. In this case, the intermediate α-hydroxy-1,2-diketone is captured by intramolecular reaction with an active substituent in the side chain ( Scheme 1B ) [ 24 25 ]. Thus, the combination of ESIPT-induced photoreactions of 3-hydroxypyran-4-one derivatives and various trapping methods opens up significant synthetic possibilities.…”
Section: Introductionmentioning
confidence: 99%